Validitas e-modul yang terintegrasi problem based learning berbasis game untuk meningkatkan keterampilan komunikasi, kolaborasi, dan berpikir kritis - Rahmawati, Nur Ita; Cintamulya, Imas (Biosfer: Jurnal Pendidikan Biologi, 2025)
Given how quickly technology is developing, 21st-century learning must connect with it and focus on giving students the skills they need to succeed in the twenty-first century. This research aims to design e-modules integrated with game-based problem-based learning to improve 21st-century skills. The research method uses the ADDIE development model, which is limited to the development stage. The validation test was conducted on four expert validators consisting of 2 researchers and two practitioners. The findings indicated that the e-module received an 83% score for its content/material component, an 84% score for its systematic component, an 83% score for its language component, and an 84% score for its visual component. With an average percentage of 84%, the e-module design met extremely valid requirements when taken as a whole. These results indicate that the e-modules that have been designed have a relatively high level of validity so that the e-module is ready to be tested without revision.